Evaluation of Magnetic Stirring and Aeration on Electrocoagulation Performance in Actual Industrial Treatment - Trinh, Dang Trung Tri; Binh, Quach An; Ty, Tran Van; Channei, Duangdao; Nakaruk, Auppatham; Khanitchaidecha, Wilawan (Frontiers in Environmental Science, 2021)
Agitation was a significant factor in achieving the high performance of the electrocoagulation (EC) system. Three EC systems with four parellal monopolar Al electrodes were established to clarify the influence of agitation methods on pollutants removal efficiency; magnetic stirring, continuous aeration, and combination of magnetic stirring and aeration. The aim of this work was to maximize industrial wastewater treatment in a short detention time and to understand the mechanisms that occurred in different EC systems. The coolant wastewater from the aluminum product industry was represented as industrial wastewater. The hybrid stirring-aeration EC system obtained a lower COD removal compared to the stirring EC system and the aeration EC system. Although aeration can cause an increase in COD removal due to complete circulation and effective coagulant formation of Fe (OH), however, the combination of aeration and stirring negatively affected the performance of CE. The possible reason was that the excessive agitation led to a rapid mixing of the solution, and then the coagulants and pollutants obtained insufficient time to form flocs to precipitate. The best EC performance was observed in the aeration EC system, followed by the stirring EC system, control system (without agitations), and the stirring aeration EC system, respectively, in the short detention time of 15 min. Furthermore, all EC systems could achieve an excellent COD removal of 91% when the detention time was sufficient (eg, 45 min for the stirring aeration EC system). Furthermore, the decreasing number of electrodes affected the COD removal efficiency, whereas the NaCl additive was insignificantly affected.